ORGANOLEPTIC EVALUATION OF BALITNAK SUPERIOR KAMPUNG CHICKENS FED BREAD WASTE - S., Wahyuningsi; Puger, A. W.; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aims to determine how the Organoleptic Evaluation of Balitnak Superior Kampung Chickens Fed Bread Waste. He research design used was a Completely Randomized Design (CRD) which consisted of 3 treatments and 5 replications where each replication contained 2 Balitnak Superior Village Chickens (KUB) with one week of age which had a homogeneous weight. The three treatments were 100% commercial ration 511 without bread waste (Treatment P0), 25% bread waste + 75% commercial ration 511 (Treatment P1) and 50% commercial ration 511 + 50% bread waste (Treatment P2). The panelists used were semi-trained panelists as many as 15 people, each of whom received 9 samples with testing based on the level of preference using a range of assessment numbers from 1 to 5. The variables observed included meat taste, meat color, meat aroma, meat texture, overall acceptance. The results showed that the organoleptic evaluation of Kampung Unggul Balitnak (KUB) chicken meat from treatment with bread waste as much as 25% and 50% had no effect on meat taste, meat color, meat aroma, meat texture, and overall acceptance. From the results of this study, it can be concluded that the organoleptic evaluation of Kampung Unggul Balitnak (KUB) chicken meat as a result of treatment with bread waste obtained the same results as the control treatment. Keywords: Kampung Unggul Balitnak (KUB) chicken, bread waste, organoleptic evaluation of meat.